2010
DOI: 10.22358/jafs/66273/2010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>Echinacea purpurea</i> and <i>Nigella sativa</i> supplementation on broiler performance, carcass and meat quality

Abstract: Present experiment was performed to study the effects of Echinacea purpurea (EP) and Nigella sativa (NS) on broiler performance, carcass and meat quality. Four treatment combinations were prepared: C -control group without any feed or water additive; E -drinking water intermittently supplemented with fermented juice of EP; N -feed supplemented with grounded seeds of NS, and EN -drinking water intermittently supplemented with EP and feed supplemented with NS. No significant treatment effect was observed on weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 7 publications
5
38
1
Order By: Relevance
“…Protein digestibility, the parameter is closely related to final output such as body weight gain, was maintained at the same value due to cage density, but it was increased significantly by the dietary inclusion of black cumin at higher levels ( Table 3). Result of the present study was in agreement with the report of Nasir and Grashorn (2010) Level of Black Cumin (%/kg) (black cumin) used in the present study might exert its improving effect on the digestive enzymes. Protein digestibility improvement of the birds fed black cumin (Nigella sativa) may probably be due to the fact that ethyl ether extracts of the seed can inhibit growth of intestinal pathogenic bacteria such as S. aurous and E. coli.…”
Section: Resultssupporting
confidence: 93%
“…Protein digestibility, the parameter is closely related to final output such as body weight gain, was maintained at the same value due to cage density, but it was increased significantly by the dietary inclusion of black cumin at higher levels ( Table 3). Result of the present study was in agreement with the report of Nasir and Grashorn (2010) Level of Black Cumin (%/kg) (black cumin) used in the present study might exert its improving effect on the digestive enzymes. Protein digestibility improvement of the birds fed black cumin (Nigella sativa) may probably be due to the fact that ethyl ether extracts of the seed can inhibit growth of intestinal pathogenic bacteria such as S. aurous and E. coli.…”
Section: Resultssupporting
confidence: 93%
“…However, results of studies concerning the use of PFA in broiler nutrition are inconsistent (Windisch et al, 2008). Some authors stated significant improvement of broiler performance (Ertas et al, 2005;Cross et al, 2007), whereas others reported no effects on BW gain and feed intake (Lee et al, 2003;Jamroz et al, 2005;Nasir and Grashorn, 2010) or feed conversion ratio (Ocak et al, 2008). These discrepancies may be due to numerous factors such as type and parts of plants used, their physical properties, time of harvest, the preparation method of PFA and their compatibility with other feed components (Jang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…At present study, adding EP extract to drinking water decreased feed intake of birds during the last weeks and also whole period of the trial. Researchers found that plant extracts had wide range of activities on digestive tract, immune and endocrine systems of birds, and some especial plants have physio-pathological (antiinflammation, anti-oxidant effect) and antimicrobial activities (Nasir & Grashorn, 2010a). The present results showed that adding EP extract to drinking water at the level of 1 or 2 mL L -1 decreased BWG of quail as compared with the control group (p < 0.05) ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with the findings of Nasir and Grashorn (2010a) who reported that broilers supplemented with EP juice significantly decreased carcass percentage as compared to control group. Also, they found that liver percent was significantly lower in EP treated birds as compared to control birds Nasir and Grashorn (2010a). Rininger, Kickner, Chigurupati, McLean and Franck (2000) stated that EP has an effect similar interferon (IFN), activating macrophages and inducing the production of interleukin (IL)-1 and IFN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation